Mr PENGARUH FLUKTUASI HARGA EMAS DAN STRATEGI PROMOSI TERHADAP MINAT NASABAH CICIL EMAS DI PEGADAIAN SYARIAH CPS BENGKULU - Riadi, Dandi; Sunarto, Andang; Alfiah, Esti (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study is motivated by the need for stable investment instruments that comply with Sharia principles. The gold installment product offered by Pegadaian Syariah has become a popular option, although customer interest is influenced by gold price fluctuations and promotional strategies. The aim of this research is to analyze the effect of these two factors on customer interest, both partially and simultaneously. The study employs a quantitative approach with an associative design, involving 150 respondents who are customers of the gold installment product at Pegadaian Syariah CPS Bengkulu, selected through simple random sampling. Data were collected using questionnaires and analyzed through multiple linear regression with SPSS version 27. The results indicate that both gold price fluctuations and promotional strategies significantly affect customer interest, whether individually or jointly. This implies that gold prices and promotions play an important role in shaping customer preferences toward the gold installment product. The study provides a theoretical contribution to the literature on consumer behavior in Islamic economics as well as practical insights for Islamic financial institutions in designing effective promotional strategies. Thus, careful management of price fluctuations and promotional activities is key to enhancing the attractiveness, competitiveness, and market position of Sharia-based investment products..